Studying Islam in practice
1 online resource (xi, 232 pages)
Keywords: "This book presents Islam as a lived religion through observation and discussion of how Muslims from a variety of countries, traditions and views practice their religion. It conveys the experiences of researchers from different disciplinary backgrounds and demonstrates the dynamic and heterogenous world of Islam. The range of fascinating case studies will help students understand how research into religious practice is carried out, and what issues and challenges arise"--